The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jpn.13115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary calcium to available phosphorus ratios on bone metabolism and osteoclast activity of the OPG /RANK/RANKL signalling pathway in piglets

Abstract: Hydroxyapatite, a mineral form of calcium (Ca) and phosphorus (P) that gives bones their rigidity, is the major and essential component of bones and teeth in the human and animal body. A suitable ratio of Ca and P is vital for bone growth. The aim of this study was to explore the effects of dietary calcium to available phosphorus ratios (Ca/AP) on bone metabolism and osteoclast activity of the osteoprotegerin (OPG)/receptor activator of nuclear factor kappa B ligand (RANKL) signalling pathway in piglets. At da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Alkaline phosphatase is mainly derived from osteoblasts and participates in inhibiting bone mineralization, increasing bone mass, and enhancing bone metabolism [52]. Inadequate P intake can promote the secretion of parathyroid hormone to improve the proliferation of osteoblasts, which results in a great deal of ALP entering the blood, thereby increasing the serum activity of ALP [53]. In this study, a lower serum ALP activity was observed in the MCP group, which is in agreement with previous reports [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…Alkaline phosphatase is mainly derived from osteoblasts and participates in inhibiting bone mineralization, increasing bone mass, and enhancing bone metabolism [52]. Inadequate P intake can promote the secretion of parathyroid hormone to improve the proliferation of osteoblasts, which results in a great deal of ALP entering the blood, thereby increasing the serum activity of ALP [53]. In this study, a lower serum ALP activity was observed in the MCP group, which is in agreement with previous reports [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…This protein can not only reflect the activity of osteoblasts but also inhibit the activity of osteoclasts and prevent bone loss [ 17 ]. PICP can reflect the synthesis rate of type I collagen and indirectly reflect the activity of bone cells and bone formation, which is conducive to the evaluation of postoperative rehabilitation of patients [ 17 , 18 ]. TRAP-5b is a glycoprotein secreted by activated macrophages, osteoclasts, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytological changes of aging bone reduce the number of osteoblasts available in bone remodeling and bone formation. Although the process of senile osteoporotic bone loss is the common result of the changes in hormone and bone cell structures, some cases of bone mass loss are just at the physiological level, while some are at the pathological level resulting from osteoporosis [ 29 , 30 ]. A SAMP6 mouse model of spontaneous senile osteoporosis was established in the present study and applied as experimental materials for investigating the regulatory effects of AR at different doses on osteoporosis administered by gavage.…”
Section: Discussionmentioning
confidence: 99%